Pengaruh Servant Leadership & Lingkungan Kerja Terhadap Kinerja Karyawan Dengan Komunikasi Efektif Sebagai Variabel Moderasi - Halimin, Iwan Sugandi; Assa, Adrie Frans (Jurnal Ilmu Manajemen Terapan, 2025)
This study aims to analyze the influence of servant leadership and work environment on employee performance, with effective communication as a moderating variable at PT Accelist Lentera Indonesia. The research employed a quantitative approach by distributing questionnaires to 80 respondents, with data analyzed using SmartPLS 4. The findings reveal that the work environment has a positive and significant effect on employee performance, while servant leadership does not show a significant effect. Moreover, effective communication does not moderate the relationship between servant leadership or work environment and employee performance. These results indicate that the work environment is the dominant factor in enhancing performance, while servant leadership may not be effective without the support of other factors. The study recommends improving the quality of the work environment and strengthening organizational communication skills to achieve optimal performance outcomes.